A diamond in the rough desert shrublands of the Great Basin in the Western United States: A new cryptic toad species (Amphibia: Bufonidae: Bufo (Anaxyrus)) discovered in Northern Nevada - Gordon, Michelle R.; Simandle, Eric T.; Tracy, C. Richard (Zootaxa, 2017)
We describe a new species of toad from the Great Basin region of northern Nevada belonging to the Bufo (Anaxyrus) boreas species complex. This cryptic species was detected through genetic analyses of toad populations sampled throughout the Great Basin and the morphological evidence was quantified through extensive sampling of live toads within the region. The new species has the smallest body size in the species complex, and can be further diagnosed from other species in the complex by its large tibial glands and unique coloration. The known distribution of the new species is restricted to an area less than 6 km2 in Dixie Valley, Churchill Co., Nevada. The Great Basin is an arid region where aquatic resources are both rare and widely scattered, making habitat suitable for anuran populations highly vulnerable to anthropogenic change. The habitat occupied by this newly described species is threatened by the incipient installation of geothermal and solar power development projects that require the water that defines its habitat.